Power pilferage detection and identification system - Rashid, Hasib Mahmudur; Rahman, Md Musfiqur; Tonmoy, Ajharul Hossain; Prottay, Mahmud Yasin (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2022.